Workshop Penulisan Penelitian Tindakan Kelas (PTK) dan Artikel Ilmiah Bagi Guru Di SMAN 1 Dawarblandong Mojokerto - Ladyawati, Erlin; Prayitno, Sunyoto Hadi; Prayogo, Prayogo; Putri, Rani Kurnia; Ningsih, Ninik Mutia (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this service program is to assist teachers in compiling and making scientific papers, especially PTK. The targets of the 2020-2021 Odd Semester Program Pengabdian kepada Masyarakat (PPM) Activities carried out by the Lecturer Team of the Mathematics Education Study Program of the Faculty of Science Technology are all teachers at SMAN 1 Dawarblandong, Mojokerto Regency. There are three stages in the implementation of the Program Pengabdian kepada Masyarakat, namely the planning stage, the socialization stage, and the implementation stage. The three stages of implementing the PTK were carried out on August 18 to September 11 2020. This PPM activity was attended by all 53 teachers of SMAN 1 Dawarblandong, Mojokerto Regency. The implementation of the Program Pengabdian kepada Masyarakat activities by the Mathematics Education Lecturer team at the PGRI Adi Buana University Surabaya went smoothly. The participants were very enthusiastic about participating in every scheduled activity. The obstacle faced during the implementation was the lack of internet bandwidth because all the teachers and resource persons used the school's internet network, but this did not dampen the participants' interest in following the activity properly and until it was finished. The conclusion that can be conveyed from the results of the Program Pengabdian kepada Masyarakat (PPM) is that the activity runs smoothly despite several obstacles. The first activity is explaining the basic concepts of the PTK, writing the PTK proposal, and the activities of the PTK, the second activity is the writing of the PTK Final Report, and the third activity is the Writing of the PTK Scientific Articles.